Influence of community structure on cooperative dynamics in coupled socio-ecological systems - Chung, Ning Ning (2015)
We explore the influence of community structure on the effectiveness of social sanction in promoting cooperative behavior in populations sharing common pool resources. We found that the formation of community within a population is not necessarily associated with a higher level of cooperation. In fact, our results show that defectors tend to survive better in populations with weak community structure. Nonetheless, as we further strengthened the community structure within a social network, we uncovered the occurrence of a transition towards a regime of greater cooperation. In this respect, our results provide deeper insights into the manner in which governance structures can have important influence on the management of coupled socio-ecological systems.